TABOO OR NOT TABOO: (IN)VISIBILITIES OF DEATH, DYING AND BEREAVEMENT - Hård af Segerstad, Ylva; Bell, Jo; Giaxoglou, Korina; Pitsillides, Stacey; Yeshua-Katz, Daphna; Cumiskey, Kathleen; Hjorth, Larissa (AoIR Selected Papers of Internet Research, 2020)
The notion that ‘death is a taboo’ pervades private, public and academic discourses around death, dying and bereavement in contemporary Western societies. The rise of digital media within the last decades further complicates the appreciation of the stance that death is a taboo, given the increased opportunities afforded in social media environments for embracing death, fostering new intimacies with strangers and semi-strangers but also for turning death into a spectacle (Jakobsen, 2016). The study of death-related practices online and the tensions they raise has rapidly been growing in the interdisciplinary field of Death online studies. However, in this field there is a need for developing shared conceptual and analytical frameworks and ensure methodological and theoretical robustness in line with developments in the study of social media communication. There is a need to synthesize insights from death sociology and interdisciplinary death online studies in order to shape an agenda for an integrated study of the offline and the online that can capture continuities and shifts in death-related practices (see also Borgstrom and Ellis, 2017). This panel collects four papers presented by six interdisciplinary scholars from Denmark, Sweden, Israel and the UK. Focusing on the (in)visibilities of death, dying and bereavement across contexts - online and offline - the papers critically revisit the ‘death is taboo’ thesis by investigating the particular conditions under which death, dying and bereavement are talked about, storied, and made socially visible and the ways in which technology plays a vital part in coping with mortality.